Association between maternal depression and neonatal outcomes: Evidence from a survey of nationally representative longitudinal studies - Li, Haoran; Ning, Wei; Zhang, Ning; Zhang, Jingya; He, Rongxin; Mao, Ying; Zhu, Bin (Frontiers in Public Health, 2022)
Abstract Background and Aims: Maternal depression before and after delivery has dramatically increased in China. Therefore, this study aimed to examine the association between antepartum and postpartum depression and neonatal outcomes. Design: A population-based retrospective cohort study. Setting: China. Participants: Data were obtained from China Family Panel Studies (CFPS). Mothers in CFPS2012 and CFPS2016, which were linked with 1–2-year-old children in CFPS2014 and CFPS2018, respectively, and mothers in CFPS2012, CFPS2016, and CFPS2018, which were linked with 0–1-year-old infants in CFPS2012, CFPS2016, and CFPS2018, respectively, were included in this study. Methods: The neonatal outcomes included duration of gestational days, preterm birth, birth weight, birth weight z-score, weight, weight z-score, illness in the past month, and hospitalization in the past year. Propensity score matching was used to balance maternal, family, and infant/child characteristics between the maternal depression and non-maternal depression groups. Results: Multivariable regression analysis of matched samples estimated that antepartum depression was associated with a shorter duration of gestation by 5.78 days (95% confidence interval [CI]=-9.45, 2.12), higher odds of preterm birth (odds ratio [OR]=2.65, 95% CI=1.08, 6.48), and the birth weight z-score (OR=1.47, 95% CI=1.02, 2.11). The association between antenatal depression and birth weight was not statistically significant. Postpartum depression was associated with more episodes of illness in the last month by 0.22 times (95% CI=0.09, 0.34) and a higher odds of hospitalization in the previous year (OR=1.47, 95% CI=1.07, 2.03). The association between postpartum depression and weight or the weight z-score was not significant. Conclusion: Maternal depression appears to be associated with worse neonatal outcomes.